Managerial ties as determinant of social entrepreneurial intentions: Does gender make a difference?. Issue 2 (8th June 2020) - Latif, Mafia; Ali, Sumran
Abstract : The notions of social entrepreneurship and social enterprise have been the emerging trends in the world today, specifically in developing countries. We draw on social network theory to explore causes and situations that encourage individuals to engage in social activities in an entrepreneurial manner. This article investigates the impact of business ties and political ties on SEIs and how gender influences the casual relationships. Linear regression is used to analyze the responses obtained from 300 general populations across three developing countries including Bangladesh, India, and Pakistan. The findings show that business ties positively affect SEIs, but political ties are negatively related to SEIs. Furthermore, our results indicate that the gender influences both the positive impact of business ties on SEIs, which is greater for males, and the negative impact of political ties, which is stronger for females.